Nehemiah Gallup diary - Gallup, Nehemiah, 1751-1843.
Diary (14 pages) of Sergeant Nehemiah Gallup kept during his service in the Connecticut Continental line relating to a march from Groton, Conn., to White Plains, N.Y., engagements near White Plains, and routine military matters.
Sergeant in the Connecticut Continental line.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: United States. -- Continental Army; Connecticut -- History -- Revolution, 1775-1783.; New York (State) -- History -- Revolution, 1775-1783.; White Plains (N.Y.) -- History; Soldiers